Novel methods for estimating the instantaneous and overall COVID-19 case fatality risk among care home residents in England - Overton, Christopher E.; Webb, Luke; Datta, Uma; Fursman, Mike; Hardstaff, Jo; Hiironen, Iina; Paranthaman, Karthik; Riley, Heather; Sedgwick, James; Verne, Julia; Willner, Steve; Pellis, Lorenzo; et al. (PLoS computational biology, 2022)
The COVID-19 pandemic has had high mortality rates in the elderly and frail worldwide, particularly in care homes. This is driven by the difficulty of isolating care homes from the wider community, the large population sizes within care facilities (relative to typical households), and the age/frailty of the residents. To quantify the mortality risk posed by disease, the case fatality risk (CFR) is an important tool. This quantifies the proportion of cases that result in death. Throughout the pandemic, CFR amongst care home residents in England has been monitored closely. To estimate CFR, we apply both novel and existing methods to data on deaths in care homes, collected by Public Health England and the Care Quality Commission. We compare these different methods, evaluating their relative strengths and weaknesses. Using these methods, we estimate temporal trends in the instantaneous CFR (at both daily and weekly resolutions) and the overall CFR across the whole of England, and dis-aggregated at regional level. We also investigate how the CFR varies based on age and on the type of care required, dis-aggregating by whether care homes include nursing staff and by age of residents. This work has contributed to the summary of measures used for monitoring the UK epidemic.